2007
DOI: 10.1017/s1326011100004439
|View full text |Cite
|
Sign up to set email alerts
|

Creating Culturally-Safe Schools for Māori Students

Abstract: In order to better understand the present trends in New Zealand's schooling contexts, there is a clarion call for educators to develop sensitivity and sensibility towards the cultural backgrounds and experiences of Ma -ori students. This paper reports on the work of four scholars who share research that has been undertaken in educational settings with high numbers of Ma -ori students, and discusses the importance of creating culturally-safe schools -places that allow and enable students to be who and what they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 6 publications
(3 reference statements)
0
81
0
Order By: Relevance
“…There is a rigorous body of research-based literature on culturally responsive pedagogy that is germane to Aotearoa New Zealand where the majority of Māori and Pasifika learners are being taught in mainstream schools where they are the minority (Bishop & Berryman, 2006;Bishop et al, 2009;Durie, 2001;Macfarlane, Glynn, Cavanagh, & Bateman, 2007). This literature is unique to other research on culturally responsive pedagogy because, in Aotearoa, there are Māori educational contexts where whakaaro Māori are normalised (e.g., kōhanga reo, kura, wānanga).…”
Section: Culturally Responsive Pedagogymentioning
confidence: 99%
“…There is a rigorous body of research-based literature on culturally responsive pedagogy that is germane to Aotearoa New Zealand where the majority of Māori and Pasifika learners are being taught in mainstream schools where they are the minority (Bishop & Berryman, 2006;Bishop et al, 2009;Durie, 2001;Macfarlane, Glynn, Cavanagh, & Bateman, 2007). This literature is unique to other research on culturally responsive pedagogy because, in Aotearoa, there are Māori educational contexts where whakaaro Māori are normalised (e.g., kōhanga reo, kura, wānanga).…”
Section: Culturally Responsive Pedagogymentioning
confidence: 99%
“…The students stated that they enjoyed learning te reo Māori because their teachers created an environment where they felt safe being Māori. The students were steadfast in their belief that their teacher was sincerely concerned about their welfare and this helped create a safe and comfortable environment [19]. Cultural education outside of the classroom further encouraged students to continue learning te reo Māori [20].…”
Section: Teaching and Learningmentioning
confidence: 99%
“…Alton-Lee (2003) found that teaching in ways that are responsive to student diversity and cultural identity can have a positive impact on low and high achievers at the same time. According to Macfarlane et al (2007), 'All students benefit from being in a culturally inclusive classroom. However many students from non-dominant cultures are not free to be whom and what they are when they go to school' (71).…”
Section: Culturally Responsive Pedagogymentioning
confidence: 99%